Data Privacy, What Still Need Consideration in Online Application System? - Dewi Puspa; Adhiawan Soegiharto; Achmad Nizar Hidayanto; Qorib Munajat (Jurnal Sistem Informasi, 2020)
This paper aims to conduct an analysis and exploration of matters that still needs to be considered in relation to data privacy in the online application system. This research is still a preliminary study. We conduct research related to data privacy using systematic literature review approach (SLR). Bt using SLR stages, we made a synthesis of 44 publications from Scopus Database Online that were released in the range 2015 - 2019. Based on this study, we found six things points to consider in data privacy, namely security and data protection, user awareness, risk managment, control setting, ethics, and transparency.